Enhancing teacher commitment through academic supervision and school climate - Yulianti, Lili; Rifma, Rifma; Yahya, Yahya; Syahril, Syahril (Indonesian Research Journal in Education |IRJE|, 2026)
This study aimed to analyze the contribution of academic supervision and school climate to teacher commitment at a public elementary school in Gunung Tuleh District, West Pasaman Regency. The approach employed was a quantitative descriptive design with an ex post facto approach and a correlational study. The study population was 254 civil servant teachers, and 102 teachers were sampled using stratified proportional random sampling. The research instrument was a closed-ended questionnaire using a Likert scale. The analysis revealed that academic supervision contributed 5.4%, school climate contributed 19.3%, and the combined effect of both factors contributed 21.5% to teacher commitment. This indicates that academic supervision and school climate have a substantial impact on teacher commitment. This study emphasizes the importance of optimizing the principal's role in implementing academic supervision and creating a conducive school climate to enhance the quality of basic education through teacher commitment.